Acoustic and temporal aspects of oesophageal speech - J.N, Sanyogeetha (Journal of All India Institute of Speech and Hearing)
Speech is a multidimensional signal that elicits a linguistic association (Flanagan 1972). It is believed that human beings are specialized for speech communication, most evidently for speech production. Surgical removal of larynx - LARYNGECTOMY - leaves the operated individual - LARYNGECTOMEE - handicapped in speech production. The speech clinician helps in the rehabilitation of the laryngectomee by developing some means of functional communication. The ’oesophageal speech’ has been traditionally considered as the method of choice.